Enhancing Antioxidant Activity in Papaya Seed Coffee (Carica papaya L.) through the Addition of Ginger Powder (Zingiber officinale Roscoe Var. officinale) - Intan Ayu Septiani; Pramudia Kurnia; Aan Sofyan (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Papaya (Carica papaya L.) seeds contain antioxidant compounds and offer potential as a raw material for functional beverages such as coffee alternatives. Their antioxidant activity may be enhanced by incorporating natural ingredients rich in bioactive compounds, such as ginger (Zingiber officinale Roscoe var. officinale), which contains high levels of phenolics. Objective: This study aimed to evaluate the effect of adding ginger powder on the antioxidant activity of papaya seed coffee.Methods: A laboratory-based quantitative experiment was conducted using a Completely Randomized Design (CRD) with two treatments: K0 (100% papaya seed powder) and KJ (80% papaya seed powder + 20% ginger powder), each replicated twice. Antioxidant activity was measured using the DPPH method, and data were analyzed using IBM SPSS Statistics 27 through either a Paired T-Test or Wilcoxon test based on data distribution. Results: The addition of ginger powder significantly increased the antioxidant activity of papaya seed coffee (p < 0.05). The IC50 value for the control (K0) was 71.38 ppm, classified as “strong,” while the KJ treatment showed a lower IC50 value, indicating higher antioxidant capacity. Conclusion: Ginger powder enhances the antioxidant properties of papaya seed coffee, supporting its development as a functional beverage with added health benefits.